TANTANGAN IMPLEMENTASI GOOD GOVERNANCE MELALUI PENINGKATAN KUALITAS PELAYANAN PUBLIK DI INDONESIA - Syafruddin Pohan; Yogo Pamungkas L Tobing; Aldino Mazuda (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The main focus in the field of public administration in Indonesia is on the provision of public services. Within the framework of Good Governance, public services must meet certain minimum quality standards. The implementation of Good Governance practices in public services is of great significance because it is crucial for the improvement of public service performance to be considered important by relevant stakeholders such as the government, the public, and the business sector. Law Number 25 of 2009 concerning Public Services serves as a foundation to enhance the quality of public services provided by civil servants or the government. It is acknowledged that the evolution of services provided by the government continues, both in terms of paradigms and service formats, in line with the increasing demands from the public and changes in the Governance structure itself. In this context, creating professional public services in accordance with the principles of Good Governance becomes highly important. This is crucial given the various issues in the recent system of providing services to the public. Public services reflecting Good Governance involve various parties, including the government, the public, and the private sector, who can carry out service activities with an innovative approach while still adhering to the principles of Good Governance.